Roles of the Chr.9p21.3 ANRIL Locus in Regulating Inflammation and Implications for Anti-Inflammatory Drug Target Identification - Aarabi, Ghazal; Zeller, Tanja; Heydecke, Guido; Munz, Matthias; Schäfer, Arne; Seedorf, Udo (Frontiers in Cardiovascular Medicine, 2018)
Periodontitis (PD) is a common gingival infectious disease caused by an over-aggressive inflammatory reaction to dysbiosis of the oral microbiome. The disease induces a profound systemic inflammatory host response, that triggers endothelial dysfunction and pro-thrombosis and thus may aggravate atherosclerotic vascular disease and its clinical complications. Recently, a risk haplotype at the ANRIL/CDKN2B-AS1 locus on chromosome 9p21.3, that is not only associated with coronary artery disease / myocardial infarction (CAD/MI) but also with PD, could be identified by genome-wide association studies. The locus encodes ANRIL - a long non-coding RNA (lncRNA) which, like other lncRNAs, regulates genome methylation via interacting with specific DNA sequences and proteins, such as DNA methyltranferases and polycomb proteins, thereby affecting expression of multiple genes by cis and trans mechanisms. Here, we describe ANRIL regulated genes and metabolic pathways and discuss implications of the findings for target identification of drugs with potentially anti-inflammatory activity in general.